2013
DOI: 10.1111/and.12096
|View full text |Cite
|
Sign up to set email alerts
|

Spermicidal activity of Indian seaweeds: anin vitrostudy

Abstract: Contraceptive properties of seaweeds are still stands as lacuna; in this context, the screening of in vitro male contraceptive properties of crude ethanolic extract of Indian seaweeds against normal human sperm is carried out. In total, twelve seaweeds were screened for in vitro spermicidal activity. Among these twelve seaweeds, Halimeda gracilis showed 100% inhibition of human spermatozoa at 10 mg ml(-1) concentration in 20 s and its EC50 value was 2.05 mg ml(-1) in 20 s. Further, dose- and time-dependent spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The analysis of sperm parameters in the study of Sobhani et al (2015) demonstrated that the general and advanced motility of frozen-thawn human spermatozoa significantly increased following incubation with the extract of the Sargassum brown algae. On the other hand, twelve seaweeds were screened for in vitro spermicidal activity in the report by Prakash et al (2014). Among these twelve seaweeds, Halimeda gracilis showed 100% inhibition of human spermatozoa at 10 µg/ml in 20 s. Furthermore, doseand time-dependent spermicidal assay revealed that the sperm was completely immobilised for 20 s. Plasma membrane of sperm was damaged due to the exposure of H. gracilis extract.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of sperm parameters in the study of Sobhani et al (2015) demonstrated that the general and advanced motility of frozen-thawn human spermatozoa significantly increased following incubation with the extract of the Sargassum brown algae. On the other hand, twelve seaweeds were screened for in vitro spermicidal activity in the report by Prakash et al (2014). Among these twelve seaweeds, Halimeda gracilis showed 100% inhibition of human spermatozoa at 10 µg/ml in 20 s. Furthermore, doseand time-dependent spermicidal assay revealed that the sperm was completely immobilised for 20 s. Plasma membrane of sperm was damaged due to the exposure of H. gracilis extract.…”
Section: Resultsmentioning
confidence: 99%
“…Sperm suspension and the extracts at different concentrations were mixed at a 1:1 ratio. Sperm mobilisation was observed and noted in each of the cases at 20 s (Prakash et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, Halimeda gracilis demonstrated a 100% suppression of human sperms due to sperm’s plasma membrane being damaged at a dosage of 10 mg/ml after 20 s of contact time. A phytochemical assessment of Halimeda gracilis extracts revealed the existence of secondary metabolites, including sugar, flavonoids, alkaloids, and protein (Prakash et al 2014 ).…”
Section: Seaweed’s Use In Pharmaceuticals and Cosmeticsmentioning
confidence: 99%